2020
DOI: 10.1038/s41586-020-2008-3
|View full text |Cite|
|
Sign up to set email alerts
|

A new coronavirus associated with human respiratory disease in China

Abstract: The Pandemic situation caused due to SARS-CoV-2 causing Coronavirus Disease (CoVID-19) around globe. Recent, COVID-19 main protease complex (M pro), highly modulating enzyme in SARS-CoV-2 was reported for viral replication and transcription. This multifunctionality of M pro attracts for identi cation of potential drug target. Considering impact, In silico analysis was performed for Palmatine alkaloid against M pro. Naturally, present in Tinospora cordifolia, found effective against Cancer, HIV, viral infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

84
10,690
8
301

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11,087 publications
(11,083 citation statements)
references
References 43 publications
84
10,690
8
301
Order By: Relevance
“…The genomic structure is shown in Fig. 7 and shows greater than 99.9% consistency [19,[91][92][93][94][95].…”
Section: The Genomic Structure Of Sars-cov-2mentioning
confidence: 99%
See 1 more Smart Citation
“…The genomic structure is shown in Fig. 7 and shows greater than 99.9% consistency [19,[91][92][93][94][95].…”
Section: The Genomic Structure Of Sars-cov-2mentioning
confidence: 99%
“…The phylogenetic tree based on whole genomes showed that SARS-CoV-2 is most closely related to bat SARS-like coronavirus bat-SL-CoVZC21 (NCBI accession number MG772934) and bat-SL-CoVZC45 (NCBI accession number MG772933), which share~89% sequence homology [91][92][93]. Their genomic organization is typical of a lineage B beta coronavirus.…”
Section: The Genomic Structure Of Sars-cov-2mentioning
confidence: 99%
“…The sliding window was set to 500 for ORF1ab and S, and to 50 for proteins E, M, and N considering their short length. SARS-CoV-2 were highly similar to RaTG13 isolated from bats, showing 96% identity based on the whole-nucleotide sequences and 83% based on the protein 3 sequences, suggesting a bat zoonotic origin of SARS-CoV-2. ORF1a, and the head of S seemed to have diverged from other beta coronaviruses.…”
Section: Dear Editormentioning
confidence: 84%
“…By February 14, 2020, a total of 66,576 2 confirmed cases of COVID-19, people infected with SARS-CoV-2, were reported in China, leading to 1,524 deaths, per the Chinese CDC (http://2019ncov.chinacdc.cn/2019-nCoV/). Several full genomic sequences of this virus have been released for the study of its evolutionary origin and molecular characteristics [2][3][4]. Here, we analyzed the potential mutations that may have evolved after the virus became epidemic among humans and also the mutations resulting in the human adaptation.…”
Section: Dear Editormentioning
confidence: 99%
“…As of Feb 16, 2020 (24:00, GMT+8), there have been 70548 confirmed patients and more than 1700 deaths from SARS-CoV-2 infection in China, and 58182 confirmed patients and 1696 deaths in the most affected province, Hubei Province. Much research progress has been made in dissecting the evolution and origin of SARS-CoV-2 and characterizing its clinical features [3][4][5][6][7] .…”
mentioning
confidence: 99%